ERP correlates of prosody and syntax interaction in case of embedded sentences. (February 2016) - Honbolygó, Ferenc; Török, Ágoston; Bánréti, Zoltán; Hunyadi, László; Csépe, Valéria
Abstract: Understanding spoken language depends on processing the delicate combination of grammatical structure, meaning and prosody of utterances. Previous studies have established that prosody influences the processing of sentences when the grammatical structure is ambiguous, however it is unclear how closely prosody and syntax are related when there is no ambiguity. In an event-related brain potential (ERP) study, we investigated the processing of embedded normal and pseudosentences in which all function and content words were replaced by meaningless words. Sentences could have either natural prosodic structure or incongruent prosodic structure, where the prosody deviated from the one expected based on the syntactic structure, but otherwise the sentences were unambiguous. The resulting ERP components (CPS) showed that the construction of prosodic structure was similar in normal and pseudosentences, thus suggesting that prosody has an abstract, recursive representation, independent of other linguistic information. Moreover, we found evidence that the incongruent prosody was not only detected (shown by the RAN), but it induced neural reintegration processes (shown by the P600) in spite of the syntactic structure of sentences being intact. These results suggest that the prosodic structure is a mandatory constituent of sentence structure building whenever it is present. Highlights: We presented embedded sentences with an incongruent prosodic structure. ERP correlates (RAN, P600) of processing prosody–syntax interaction were measured. We replicated the CPS component in Hungarian in both normal and pseudosentences. ERP components indicated the detection and integration effort of incongruent prosody. Results suggest that prosody is a mandatory constituent of parsing.